(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Women’s role in Pre-colonial social structures revealsthat feminism was theorized differently in India than in the West. InIndia, women’s issues first began to be addressed when the state commissioned areport on the status of women to a group of feminist researchers and activists.The report recognized the fact that in India, women were oppressed under asystem of structural hierarchies and injustices. During this period, Indianfeminists were influenced by the Western debates being conducted about violenceagainst women. However, due to the difference in the historical and socialculture of India, the debate in favor of Indian women had to be conductedcreatively and certain Western ideas had to be rejected.[9] Women’sissues began to gain an international prominence when the decade of 1975–1985was declared the United Nations Decade for Women.